2015
DOI: 10.1039/c5fo00496a
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of grape seed procyanidin B2 on a diabetic pancreas

Abstract: The prevalence of type 2 diabetes mellitus (T2DM) has increased considerably in recent years, highlighting the importance of developing new therapeutic strategies. Insulin-resistance and gradual dysfunction of pancreatic islets are the mainstay in the progression of T2DM. Therefore, preserving the function of the pancreas may lead to new prospective approaches. Our previous studies suggested that grape seed procyanidin B2 (GSPB2), a natural polyphenol product, exhibited protective effects on diabetic vasculopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…To date, the upregulation of MFG‐E8 levels has been reported in db/db mice, as well as patients with T2D and chronic pancreatitis . The current investigation presented supporting evidence for the concept that T2D patients had higher MFG‐E8 serum levels than healthy controls.…”
Section: Discussionsupporting
confidence: 80%
“…To date, the upregulation of MFG‐E8 levels has been reported in db/db mice, as well as patients with T2D and chronic pancreatitis . The current investigation presented supporting evidence for the concept that T2D patients had higher MFG‐E8 serum levels than healthy controls.…”
Section: Discussionsupporting
confidence: 80%
“…This suggests a similarity in alteration in MFG‐E8 activity that was found in the myometrium, as well as in the endometrium during human pregnancy, which was probably due to MFG‐E8 functioning as an extracellular growth factor during gestation that promoted expansion of the connective tissue framework supporting the hypertrophied bundles of smooth muscle. Furthermore, we established that the plasma concentrations of MFG‐E8 were greater in GDM than that observed in normal pregnant women, which was in consist with the elevated MFG‐E8 levels that have been confirmed in db / db mice and type 2 diabetes patients. However, the exact mechanism of elevated MFG‐E8 concentrations during human gestation and GDM has not been completely elucidated yet, and further research is required for it to be clearly understood.…”
Section: Discussionmentioning
confidence: 66%
“…On the other hand, recent studies have shown antiinflammatory and antioxidant effects of PB2 and EPC, which exert positive effects by improving diabetes comorbidities. They were observed to bring improvement in insulin sensitivity and to exert a protective effect against diabetic nephropathy and cardiomyopathy [20,21].…”
Section: Discussionmentioning
confidence: 99%